Neuromarkers associated with two levels of physical activity in persons with chronic conditions - Wenzell, Megan L.; Moore, Shirley M.; Still, Carolyn H.; Wierenga, Kelly L. (Journal of applied physiology (1985), 2023)
The influence of the brain on engagement in regular physical activity (PA) has not been well studied. We examined relationships between the activation of three neuromarkers and two PA levels in 58 persons self-managing chronic conditions. Findings suggest that individuals who optimally process health-information when the emotional tone is high (Empathic Network; DMN) may engage in more PA compared with individuals who respond to health information when the emotional tone is low (Analytic Network; TPN). Although research has largely focused on the effects of physical activity (PA) on the brain, less is known about the influence of the brain on engagement in healthy-living behaviors, such as regular PA. In this secondary analysis of a study of brain activity and participation in healthy-living behaviors, we examined relationships between the activation of selected brain networks and PA in persons self-managing chronic conditions. Fifty-eight individuals with chronic conditions underwent functional magnetic resonance imaging while exposed to a protocol consisting of listening to emotion-focused and analytic-focused information and measures of activation of three neuromarkers were obtained: default mode network (DMN), task-positive network (TPN), and ventromedial prefrontal cortex (vmPFC). In an exploratory analysis, we assessed differences in neuromarker activation between two PA levels (representing higher and lower accelerometry-measured PA levels) of 1) moderate-to-vigorous physical activity (MVPA) minutes, 2) metabolic equivalents expended (METs), and 3) daily steps. Results showed positive associations between MVPA and DMN ( r = 0.31, P = 0.018), steps and DMN ( r = 0.28, P = 0.035), and MVPA and vmPFC ( r = 0.29, P = 0.026). No associations were found between the TPN and any of the PA measures. Individuals with high MVPA and METs had higher DMN values compared with those with low MVPA ( t = −2.17, P = 0.035) and METs ( t = −2.02, P = 0.048). No differences in TPN and vmPFC were found among PA levels. These results suggest that providing health information that activates the emotion-focused brain network may be more useful than analytic-focused information (centered on logic and reasoning) to assist people with chronic conditions to engage in more PA. NEW & NOTEWORTHY The influence of the brain on engagement in regular physical activity (PA) has not been well studied. We examined relationships between the activation of three neuromarkers and two PA levels in 58 persons self-managing chronic conditions. Findings suggest that individuals who optimally process health-information when the emotional tone is high (Empathic Network; DMN) may engage in more PA compared with individuals who respond to health information when the emotional tone is low (Analytic Network; TPN).